Simulador YENKA como recurso didáctico para el aprendizaje de química inorgánica con los estudiantes del tercer semestre de la carrera de Pedagogía de las Ciencias Experimentales Química Biología periodo noviembre 2020 – abril 2021 - Lema Guamán, Deisy Patricia (2021)
The virtual simulators implementation in higher education has opened new learning scenarios, however, the complex way of operating them, the language in which they are commonly offered, the high cost of the product and the difficulties to understand some Inorganic Chemistry subject contents, have generated in the students a certain rejection for their study uses. The objective of this research was to propose the use of the YENKA simulator as a didactic resource to strengthen the experimental learning of Inorganic Chemistry. The methodological design was non-experimental, bibliographic and field type; meta-analysis, meta-synthesis, inductive and deductive methods. For data collection, a survey was applied to 38 third-semester students of the Pedagogy of Experimental Sciences: Chemistry and Biology through a questionnaire. When analyzing and interpreting the results, it was concluded that 79% of the students totally agree that the YENKA simulator is a didactic support tool for the study and experimental learning of Inorganic Chemistry, because it is a fully equipped and extremely flexible virtual laboratory that allows the development of experimental activities under the same characteristics of reality, facilitating the achievement of significant learning. Therefore, it is recommended to promote the use of the Yenka simulator as an efficient didactic resource to improve the learning of this science.